Analysis of Various Contexts of Difficulties Experienced by Students in Learning Physics - Rizaldi, Dedi Riyan; Fatimah, Ziadatul (Faculty of Science and Education, UIN Walisongo Semarang, 2024)
Physics is a subject that is difficult for students to learn and understand, especially at the high school level. This study identifies various factors contributing to students' difficulties teaching physics. This study used a qualitative method, with the object of research being 90 grade 12 students from five schools in the city of Mataram, namely MA Plus Nurul Islam Sekarbela, MAN 1 Mataram, MAN 2 Mataram, SMAN 1 Mataram, and SMAN 3 Mataram. The research data was collected using survey techniques, Google forms, and interview techniques and analyzed descriptively. Based on the research, it was found that almost 62% of students did not like learning physics. The wave and optical material group is the most challenging material for students to learn, with a percentage of 46%. Students ask their peers more frequently, 52%, based on their problem-solving abilities. In contrast, the form of description questions is the least popular question for students in the learning process, with a percentage value of 9%.